RESOURCE GOVERNANCE EVALUATION TO ENHANCE COMPETITIVE ADVANTAGE IN BANKING: A COBIT 5 APPROACH - Gustian Rama Putra; Wahyu Sardjono; Rafi Athallah; Andi Nurkholis (Universitas Teknokrat Indonesia, 2023)
Bank XYZ is a bank that has been standing for more than 40 years and is engaged in giving the best of financial services. The company has been improving the use of IS/IT within the company for the past few years to support and elevate their business process to the next level and gaining competitive advantages in the banking sector. Within the development of there IS/IT services, the company stumbled on a few problems regarding IT resources used in the company. For this reason, in this study, the researcher took measurements of the levels of capability in IT Resource governance using the COBIT 5 framework as a standard framework for IT governance. The result of this research showed that the average enterprise capability is still at level 1 (performed) where the company’s target is level 3 (established)